Α1-antitrypsin deficiency and inflammation. (March 2011) - Ekeowa, Ugo I; Marciniak, Stefan J; Lomas, David A
Α1 -antitrypsin deficiency is an autosomal recessive disorder that results from point mutations in the SERPINA1 gene. The Z mutation (Glu342Lys) accounts for the majority of cases of severe α1 -antitrypsin deficiency. It causes the protein to misfold into ordered polymers that accumulate within the endoplasmic reticulum of hepatocytes. It is these polymers that form the periodic acid Schiff positive inclusions that are characteristic of this condition. These inclusions are associated with neonatal hepatitis, cirrhosis and hepatocellular carcinoma. The lack of circulating α1 -antitrypsin exposes the lungs to uncontrolled proteolytic attack and so can predispose the Z α1 -antitrypsin homozygote to early-onset emphysema. α1 -antitrypsin polymers can also form in extracellular tissues where they activate and sustain inflammatory cascades. This may provide an explanation for both progressive emphysema in individuals who receive adequate replacement therapy and the selective advantage associated with α1 -antitrypsin deficiency. Therapeutic strategies are now being developed to block the aberrant conformational transitions of mutant α1 -antitrypsin and so treat the associated disease.